Instrument development for integrating character education in ELT materials: Students"™ needs survey - Ciptaningrum, Dyah Setyowati; Fadhlia, Hilda Nur; Jinabe, Megan; Kalatingal, Hameeda; Yu, Zhao (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
In addition to acquiring language skills, English students need to develop character to become responsible global citizens. Learning materials play a crucial role in building students"™ competencies, making it essential to integrate character education (CE) into English language teaching (ELT) materials. This study aims to develop valid and reliable survey instruments to collect data on students"™ needs for designing CE-integrated materials. Using the MEASURE approach, the instrument framework is based on ELT and CE theories. A pilot survey was conducted, and Cronbach"™s Alpha and Confirmatory Factor Analysis (CFA) were used to ensure reliability and validity. The results confirm the instrument"™s suitability for larger-scale application to assess students"™ needs for CE in classrooms. Researchers and educators can use this tool to gain insights into student expectations and gaps in CE integration. Future research is recommended to test the instrument at different educational levels and to develop complementary instruments capturing teachers"™ perspectives to further enhance the integration of CE in ELT.